Variation and specialization of repeats in budding yeast - Babokhov, Michael. (2018)
Abstract: Tandem repeats are unique DNA sequences that consist of repeating motifs arranged end-to-end in the genome. When present in open reading frames, tandem repeats can significantly impact protein function through several unique mechanisms. Although previously overlooked, tandem repeats are now well-appreciated for their role in gene and protein regulation. However, studies up until now have mostly focused on only a subset of tandem repeats and a more complete understanding of repeats requires further detailed examination of their structure and function. The work presented in this thesis leverages the power of yeast genetics to address two fundamental questions of repeats in protein-coding sequences: 1) what is the extent and purpose of repeat variation? 2) what is the extent of specialization versus redundancy in tandem repeats? To address the first question, high quality genomic sequences of almost 100 strains and species of budding yeast were examined to look for instances of repeat variation. Tandem repeats were found to be variable, highly conserved and correlated with regions of intrinsic disorder. To answer the second question, a repeat in the largest subunit of RNA polymerase II was investigated in depth to look for instances of repeat specialization. Certain repeats demonstrated specific functions and these functions were tied to genetic and physical interactions with key co-transcriptional factors. Taken together, these results characterize surprising new aspects of tandem repeat function and lay the foundation for further studies into repeat variation and specialization. Future perspectives are also discussed, highlighting promising new directions in the study of tandem repeats and their impact on protein structure and function.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Biology.; Advisor: Stephen Fuchs.; Committee: Susan Ernst, Juliet Fuhrman, Jason Kuehner, and Kelly McLaughlin.; Keyword: Biology.